Experimental and Numerical Study of Two Dimensional Flow of Bubble Separation over the Leading of Thickness Plate - Herman Sasongko; Abdul Haris Irfani (JMES The International Journal of Mechanical Engineering and Sciences, 2020)
Various design modifications made by transportation equipment companies aim to increase the efficiency of fuel consumption. One of them is by reducing the drag force. This can be done by controlling passive turbulent boundary layers. The addition of rounded shape on the leading edge which is correlated with the length of the plane is one way of controlling the passive turbulent boundary layer which can accelerate the transition from the laminar boundary layer to the turbulent boundary layer. Therefore, this study aims to determine the effect of the Reynolds number and flow support length on the flow characteristics so that the downstream separation can be delayed. This research was conducted by experimental and numerical methods. The Reynolds number used is Ret = 5.08 × 104 and Ret = 8.46 × 104 . The test part of this research is the rounded leading edge of thick plate with a plane length of c/t = 6.5 and c/t = 10. The amount of rounded on the leading edge, the height of the test model and the length of the trailing edge are 10 mm, 100 mm, and 300 mm, respectively. The parameters varied in this study were the flow bearing field length (c/t) and the Reynolds number (Ret). Two-dimensional, steady numerical simulation was carried out using ANSYS Fluent software. The turbulence model used is k − kl − ω. The results obtained in this study are the longer the flow bearing plane and the greater the Reynolds number can delay the separation on the upper side of the circular front edge of the thick plate. The optimal length of the separation delay time is c/t = 10 with Ret = 8.46 × 104 .The separation bubble profile at c/t = 10 with Ret = 8.46 × 104 has length (x/c) = 0.129, thickness (y/t) = 0.1363, and angle (Θ) = 30.3 ◦ with the form factor (H) at point O 1.424. Overall the optimal variation is at c/t = 10 with Ret = 8.46 × 104 where the point of separation occurs when x/c = 0.945.